Use of equipment and respite services and caregiver health among Australian families living with Rett syndrome - Urbanowicz, A.; Downs, Jennepher; Bebbington, A.; Jacoby, P.; Girdler, S.; Leonard, H. (Elsevier Inc., 2011)
This study assessed factors that could influence equipment and respite services use among Australian families caring for a girl/woman with Rett syndrome and examined relationships between use of these resources and the health of female caregivers. Data was sourced from questionnaires completed by families (n = 170) contributing to the Australian Rett Syndrome Database in 2004 and 2006. Regression analysis was used to assess relationships between child factors (age, mobility, clinical severity and behaviour), family factors (accessibility and socio-economic factors) and the use of equipment and respite services in 2004, and relationships between resource use in 2004 and health of female caregivers as measured by the SF-12 in 2006. In 2004, the majority (88.3%) of families used at least one piece of equipment with more equipment use associated with greater mobility restrictions. Home respite services were used by 54.9% of families and overnight respite services by 47.6% of families. Use of more home respite services was associated with severely restricted levels of mobility and mothers having a vocational or university qualification. Use of more overnight respite services was associated with increasing age of the girl/woman with Rett syndrome and mothers being employed while use of less overnight respite services was associated with increasingly difficult behaviours in the girl/woman.In 2006, female caregivers had a mean mental health score of 41.1 (95% CI 38.9–43.3) and no relationships with previous resource use were identified. The mean physical health score of female caregivers was 48.7 (95% CI 46.8–50.5) and lower scores were associated with the use of equipment and overnight respite services. Equipment was a widely used resource whereas respite services, particularly overnight services, were used less widely. Further investigation of the reasons for this and alternative support strategies is indicated.